Valproate Sodium Protects Blood Brain Barrier Integrity in Intracerebral Hemorrhage Mice. (11th November 2020) - Zhao, Wei; Zhao, Lianhua; Guo, Zaiyu; Hou, Yanwei; Jiang, Jiafeng; Song, Yijun
Abstract : Valproate sodium (VPA) is a traditional antiepileptic drug with a neuroprotective role in cerebrovascular disease. After intracerebral hemorrhage (ICH), mechanical compression by hematoma, neuroinflammation, oxidative stress, and cytotoxicity of hematoma lysates caused the destruction of the blood brain barrier (BBB). Targeting BBB is a major therapeutic method for patients with ICH. The purpose of the present study was to explore the role of VPA in preserving BBB integrity in the ICH model and investigate the underlying molecular mechanisms. One hundred and thirty-six adult male CD1 mice were randomly divided into five groups in the study. Mice subjected to ICH were administered intraperitoneally with VPA at 3, 24, and 48 h post-ICH, respectively. Neurobehavioral assessments, BBB permeability, Evans blue fluorescence, hematoma volume, and protein expression were evaluated. The administration of VPA reduced BBB permeability and improved the neurobehavior significantly post-ICH. VPA administration significantly decreased the expression of phosphorylated nuclear factor-kappa B (p-NF κ B), matrix metalloproteinases 9 (MMP9), tumor necrosis factor α (TNF α ), and interleukin-6 (IL-6), while it enhanced the expression of claudin 5 and occludin in the brain. In conclusion, VPA administration maintained the integrity of BBB after experimental ICH, thus reducing brain edema and improving the neurological outcomes. Therefore, VPA administration might be a new therapeutic method to protect BBB integrity for patients with ICH.